The role of chemokines in liver disease - Sapuła, Klaudia; Gołacki, Jakub; Marczak, Aleksandra; Hordejuk, Michalina; Iwaszko-Sochal, Klaudyna (Journal of Education, Health and Sport, 2022)
Chemokines are involved in many processes, including the normal immune response to infection, as well as pathological processes such as carcinogenesis, autoimmunity and inappropriate inflammatory responses. These processes represent an important aspect in the context of liver disease, its progression and the possibility of inhibiting fibrosis. Chemokines belong to low molecular weight proteins with a wide range of functions affecting cell migration, involving different physiological and pathological processes. Depending on whether they participate in the maintenance of homeostasis during periods of well-being or represent a type of intervention of the organism to its disorders, their secretion by cells is constitutive or induced. This article focuses on the classification, structure and functions of these molecules and their possible involvement in the pathogenesis of liver diseases, as well as the possibilities of therapeutic application of this knowledge.